Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Cumulative Review: 11

Answer

$x = -1$ and $y=-3$

Work Step by Step

Given the equations $5x - y = -2$ and $y = 3x$ Substituting the $y$ in the first equation, we have: $5x - y = -2 \longrightarrow 5x - 3x = -2$ Therefore, we have: $5x - 3x = -2 \longrightarrow 2x = -2 \longrightarrow x = \dfrac{-2}{2}\longrightarrow x = -1$ Substituting $x$ in the second equation, we have: $y = 3x \longrightarrow y = 3(-1) \longrightarrow y = -3$ Verifying: First equation: $5x - y = -2 \longrightarrow 5(-1) - (-3) = -2 \longrightarrow -5 + 3 = -2 \longrightarrow -2 = -2$ Second equation: $y = 3x \longrightarrow -3 = 3(-1) \longrightarrow -3=-3$ Therefore the solution is: $x = -1$ and $y=-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.